2004
DOI: 10.1063/1.1669052
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient probe with a wedge-shaped metallic plate for high density near-field optical recording

Abstract: The distribution of the optical near-field generated by a probe with a wedge-shaped metallic plate was calculated using a finite difference time domain method. The dependence of the distribution on the size and the material of the metallic plate was calculated, and it was shown that a strong optical near-field was generated at the apex of the metallic plate when the size and the material were optimized so that a surface plasmon was excited in the metallic plate. The influence of the recording medium was also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Necessary to this end, it is required to deliver the optical energy to a sub-100-nm spot size, i.e., far beyond the diffraction limit of optical light. The most successful approaches include localization of the evanescent light from near-field optical probes [13], using metallic plates to excite surface plasmons [14,15] or a combination thereof [16].Here, we implement time-resolved Fourier transform holography (FTH) [17] and exploit x-ray magnetic circular dichroism (XMCD) to directly image the magnetization dynamics induced by a deliberately spatially localized excitation via an optical standing wave. In addition to a spatially confined reduction of the magnetization and its subsequent slower recovery, evidence is found for concurrent changes in the spatial magnetization profile, suggesting the presence of ultrafast lateral transport of spin-polarized electrons on a nanometer length scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Necessary to this end, it is required to deliver the optical energy to a sub-100-nm spot size, i.e., far beyond the diffraction limit of optical light. The most successful approaches include localization of the evanescent light from near-field optical probes [13], using metallic plates to excite surface plasmons [14,15] or a combination thereof [16].Here, we implement time-resolved Fourier transform holography (FTH) [17] and exploit x-ray magnetic circular dichroism (XMCD) to directly image the magnetization dynamics induced by a deliberately spatially localized excitation via an optical standing wave. In addition to a spatially confined reduction of the magnetization and its subsequent slower recovery, evidence is found for concurrent changes in the spatial magnetization profile, suggesting the presence of ultrafast lateral transport of spin-polarized electrons on a nanometer length scale.…”
mentioning
confidence: 99%
“…Necessary to this end, it is required to deliver the optical energy to a sub-100-nm spot size, i.e., far beyond the diffraction limit of optical light. The most successful approaches include localization of the evanescent light from near-field optical probes [13], using metallic plates to excite surface plasmons [14,15] or a combination thereof [16].…”
mentioning
confidence: 99%
“…Au and Ag for the plasmon antenna showed a high intensity for generating near field optics 7) . However, when these materials are used as a plasmon antenna in the NOAH head as shown in Fig.1, their durability becomes a problem, such as in the adhesion between Au and glass, and in the oxidation of Ag.…”
Section: Double Layered Electrode For Plasmon Antennamentioning
confidence: 99%
“…In addition, Matsumoto et al reported the simulation results that resonance wavelength depends on the shape of the plasmon antenna and its materials 7) .…”
Section: Introductionmentioning
confidence: 99%
“…We previously proposed an optical near-field generator with a beaked metallic plate ͑called a "nanobeak"͒. 11,12 Marks with a diameter of 40 nm were written on a phase-change recording medium by a head with the nanobeak. In the present work, we performed a writing experiment in which we used the nanobeak to write marks on a BPM.…”
mentioning
confidence: 99%